The Gut–Immune–Brain Axis: An Important Route for Neuropsychiatric Morbidity in Inflammatory Bowel Disease - Masanetz, Rebecca Katharina; Winkler, Jürgen; Winner, Beate; Günther, Claudia; Süß, Patrick (International Journal of Molecular Sciences, 2022)
Inflammatory bowel disease (IBD) comprises Crohn’s disease (CD) and ulcerative colitis (UC) and is associated with neuropsychiatric symptoms like anxiety and depression. Both conditions strongly worsen IBD disease burden. In the present review, we summarize the current understanding of the pathogenesis of depression and anxiety in IBD. We present a stepwise cascade along a gut–immune–brain axis initiated by evasion of chronic intestinal inflammation to pass the epithelial and vascular barrier in the gut and cause systemic inflammation. We then summarize different anatomical transmission routes of gut-derived peripheral inflammation into the central nervous system (CNS) and highlight the current knowledge on neuroinflammatory changes in the CNS of preclinical IBD mouse models with a focus on microglia, the brain-resident macrophages. Subsequently, we discuss how neuroinflammation in IBD can alter neuronal circuitry to trigger symptoms like depression and anxiety. Finally, the role of intestinal microbiota in the gut–immune–brain axis in IBD will be reviewed. A more comprehensive understanding of the interaction between the gastrointestinal tract, the immune system and the CNS accounting for the similarities and differences between UC and CD will pave the path for improved prediction and treatment of neuropsychiatric comorbidities in IBD and other inflammatory diseases.
Created from Fastlane, Scopus look-up
Keywords: Crohn’s disease; depression; gut microbiota; gut-brain axis; inflammatory bowel disease; neuroinflammation; systemic inflammation; ulcerative colitis